ANALISIS PEMETAAN SEBARAN SEKOLAH LUAR BIASA (SLB) DI PROVINSI BANTEN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Azzahra, Aisyah; Akbar Mukasyaf, Aziz; Amin, Choirul; Lila Anggani, Nirma (Jurnal Spasial, 2025)
The equality of education for Children with Special Needs (CSN) remains constrained by the unequal number and spatial distribution of Special Education Schools (SLB) in Banten Province. This study aims to map the distribution of SLB by education level and analyze their spatial patterns and accessibility to road networks. A quantitative descriptive method with a Geographic Information System (GIS) approach was applied. Nearest Neighbor Analysis (NNA) was used to identify spatial distribution patterns, and Network Analysis assessed accessibility to main roads. Results indicate that SLB distribution in Banten is uneven, showing clustered patterns in Tangerang and Pandeglang, while Serang and Lebak have low accessibility. These findings highlight the importance of GIS-based spatial planning to support equitable and inclusive education development in Banten Province.